Misinterpretation of the Determinants of Elevated Forward Wave Amplitude Inflates the Role of the Proximal Aorta. Issue 2 (February 2016) - Phan, Timothy S.; Li, John K‐J.; Segers, Patrick; Chirinos, Julio A.
Abstract : Background: The hemodynamic basis for increased pulse pressure (PP) with aging remains controversial. The classic paradigm attributes a predominant role to increased pulse wave velocity (PWV) and premature wave reflections (WRs). A controversial new paradigm proposes increased forward pressure wave amplitude (FWA), attributed to proximal aortic characteristic impedance (Zc ), as the predominant factor, with minor contributions from WRs. Based on theoretical considerations, we hypothesized that (rectified) WRs drive the increase in FWA, and that the forward pressure wave does not depend solely on the interaction between flow and Zc (QZc product). Methods and Results: We performed 3 substudies: (1) open‐chest anesthetized dog experiments (n=5); (2) asymmetric T‐tube model‐based study; and (3) human study in a diverse clinical population (n=193). Animal experiments demonstrated that FWA corresponds to peak QZc only when WRs are minimal. As WRs increased, FWA was systematically greater than QZc and peaked well after peak flow, analogous to late‐systolic peaking of pressure attributable to WRs. T‐tube modeling confirmed that increased/premature WRs resulted in increased FWA. Magnitude and timing of WRs explained 80.8% and 74.3% of the variability in the difference between FWA and peak QZc in dog and human substudies, respectively. Conclusions: Only in cases of minimal reflections does FWA primarily reveal the interaction between peak aortic flow and proximal aortic diameter/stiffness. FWA is strongly dependent on rectified reflections. If interpreted out of context with the hemodynamic principles of its derivation, the FWA paradigm inappropriately amplifies the role of the proximal aorta in elevation of FWA and PP.